Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1071/rj9900054
|View full text |Cite
|
Sign up to set email alerts
|

Soil and landscape processes in the restoration of rangelands.

Abstract: A rational analytical approach to the restoration of degraded rangelands is proposed in which degradation is described in terms of loss or diminution of plant habitat favourability. The approach recognizes that fertile patches or zones are maintained by the action and interaction of abiotic and biotic transfer processes. The identity and character of these processes can be deduced from data derived from integrated vegetation and landscape surveys. Ecosystem function and disfunction can be identified and geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…However, recent work on semi-arid rangelands (Schlesinger et al, 1990;Tongway, 1990;Friedel et al, 1993) has shown that land degradation may result in increased runoff, and increased soil and water redistribution within an area. This leads to changes in the distribution pattern of different types of vegetation cover, and not necessarily a reduction in biomass.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work on semi-arid rangelands (Schlesinger et al, 1990;Tongway, 1990;Friedel et al, 1993) has shown that land degradation may result in increased runoff, and increased soil and water redistribution within an area. This leads to changes in the distribution pattern of different types of vegetation cover, and not necessarily a reduction in biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of a greater amount of pit-trapped seed and capture of eroded soil helps to trap litter in the pits (James and Eldridge, 2007), enhancing the breakdown process by bringing microbes into contact with organic matter. Because pits act as filters and retain resources in situ at fine spatial scales within runoff zones, their effect may be to uncouple runoff slopes from drainage lines, analogous to the trapping of water and sediment by arid zone vegetation (Tongway, 1990).…”
Section: Echidna Pits and The Maintenance Of Functional Woodlandsmentioning
confidence: 99%
“…This patchy distribution leads to the development of nutrient-rich 'resource islands' (Garner and Steinberger 1989) or 'fertile patches' (Tongway 1990) within which plants and animals are concentrated. Essential nutrients arrive in pulses, such as after high-intensity rainfall or massive erosion events.…”
Section: Microbiotic Crusts and The Development Of Landscape Heterogementioning
confidence: 99%